Subclinical Infection by Avian Influenza H5N1 Virus in Vaccinated Poultry - Tarigan, Simson (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Highly Pathogenic Avian Influenza (HPAI) H5N1 is endemic in Indonesia especially in unvaccinated sector-4 poultry. Considering that vaccination against influenza viruses does not induce sterilizing immunity and the source of infection is prevalent around the vaccinated farms, infection in the commercial layers and breeders may be common. Because infection in vaccinated birds is usually subclinical, its presence is unnoticable. The virus in such farms may be circulated persistently and become the source of infection to the surrounding areas. The test, Differentiation Infected from Vaccinated Animals (DIVA) that can be used to identify subclinically infected farms is not available yet in Indonesia. Observation on sentinel chicken among vaccinated birds is a sensitive and accurate method but unsafe for HPAI. The DIVA method based on heterologous neuraminidase has been successfully used in Italy, but it is difficult to be applied in Indonesia. The DIVA method based on Ectodomain protein M2 virus Influenza (M2e) uses antibody against M2e as infection marker and does not limit the subtype of vaccine used. This method is potential to be used in Indonesia because the M2e is very conserved across all avian influenza viruses and has high proportion of post-infected seroconverted birds. Key words: H5N1, DIVA test, heterologous neuraminidase, M2e, vaccination